Laser gain medium material and preparation method thereof
By mixing M ions of the Communist Party of China in the mixed titanium sapphire crystal and adjusting the concentration of titanium ion doping, the problem of titanium ion mixing difficulty in titanium sapphire crystals in the existing technology has achieved the preparation and high power of high -quality large -sized crystals and high -power crystals Laser output.
Patent Information
- Application Number
- CN202410275603.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-03-12
AI Technical Summary
The prior art is difficult to effectively increase the titanium ion doping concentration in titanium doped sapphire crystals, which leads to difficulty in preparing large-size high-quality crystals. The absorption efficiency and output power of diode-pumped titanium gem lasers are not high, which limits the low level of small titanium gem lasers. Cost and application.
By introducing m ion, a total of mixing in titanium sapphire crystals, adjusting the doping concentration of titanium ions in the AL2O3 crystal, and using high -temperature solid reaction and secondary high -temperature solid sintering. Sapphire crystal.
Effectively improve the concentration of titanium ions in titanium sapphire crystals, realize the preparation of high -quality large -sized crystals, improve the ability of diode to produce broadband adjustable laser, and reduce structural complexity, size and price.
Smart Images

Figure CN118048687B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser gain medium materials, and in particular to a laser gain medium material and a preparation method thereof. Background Art
[0002] Titanium-doped sapphire crystals have excellent thermal, mechanical and broadband emission properties and are widely used in the field of tunable and ultrafast laser technology. As one of the three basic laser crystals, titanium-doped sapphire crystals are driving laser technology towards ultra-strong and ultra-fast directions and are at the forefront of laser technology development. At present, people have achieved a maximum peak power laser output of more than 10 petawatts in titanium-doped sapphire crystals, and the size of the gain medium is 230mm. To achieve hundreds of petawatts or even higher power lasers, larger crystals are required. However, the titanium ion segregation coefficient is small (~0.14), which makes the preparation of large-sized crystals challenging. On the other hand, due to the low titanium ion doping concentration in titanium sapphire, the efficiency and output power of diode-pumped titanium sapphire lasers in absorbing pump light are generally not high, which restricts the low cost and further application of small titanium sapphire lasers. Improving the segregation coefficient and increasing the titanium ion doping concentration are the key to solving the above problems.
[0003] Generally, various methods such as the pulling method, the temperature gradient method, the kilowatt method, the heat exchange method and the flame melting method are used to grow titanium-doped sapphire crystals. Due to the large difference in radius between titanium ions and aluminum ions in sapphire, it is difficult for titanium ions to enter the sapphire lattice, resulting in abnormally difficult doping and uneven distribution of luminescent ions, making it difficult to obtain large-sized, high-quality crystals. In the crystal preparation process, the gain medium crystal uses aluminum oxide, titanium dioxide or titanium trioxide as raw materials. The objective fact that the radius of titanium ions and aluminum ions in sapphire are quite different still exists. Only by changing the preparation method or process, the problem of the abnormal difficulty of titanium ion doping cannot be solved. For example, the titanium-doped sapphire crystal is grown by the pulling method, and the crystal is light red, and the color of the crystal gradually deepens from the seed crystal to the tail. Through experimental tests, the titanium ion concentration in the seed crystal part of the crystal is very low, about ~0.05wt.%, which makes it difficult to achieve effective laser diode pumping and ultrafast high-power laser output of the crystal. If the titanium-doped sapphire crystal is grown by the heat exchange method, the crystal is easy to crack and the size of use is limited. For example, when titanium-doped sapphire crystals are grown by flame melting, the quality of the crystals is poor, and it is difficult to achieve laser oscillation and light amplification. In order to meet the new demand for gain media in diode-directly pumped titanium-doped sapphire wide-tunable lasers and the development of 100-petabawatt or even higher-power lasers, it is urgent to solve the key problem of titanium ion doping difficulties. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the object of the present invention is to provide a method for preparing a laser gain medium material, by introducing M ions to effectively increase the titanium ion doping concentration in the titanium-doped sapphire crystal.
[0005] Another object of the present invention is to provide a laser gain medium material prepared by the above preparation method.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a laser gain medium material comprises the following steps:
[0008] (1) Press (Al 1-x-y Ti x M y )2O 3-δ Weighing materials containing aluminum ions, materials containing titanium ions, and materials containing M ions;
[0009] The M ions are used to adjust the doping concentration of titanium ions in the Al2O3 crystal, which is Be 2+ 、Na + , K + Mg 2+ , Rb + , Ca 2+ , Sr 2+ , Ba 2+ One or any combination of
[0010] x = 0.10% to 3%, which is the molar percentage of titanium ions in the total cations;
[0011] y = 0.10% to 3%, which is the molar percentage of M ions in the total cations;
[0012] δ is the change in the number of oxygen ions caused by the change in the valence state of M ions, δ>0%;
[0013] (2) grinding and mixing the materials weighed in step (1) and then subjecting them to a high-temperature solid-phase reaction to obtain sapphire powder co-doped with M ions and titanium ions;
[0014] (3) pressing the sapphire powder co-doped with M ions and titanium ions into tablets and performing secondary high-temperature solid-phase sintering;
[0015] (4) Using the Czochralski method or other high-temperature melt crystal growth methods to grow crystals, sapphire crystals co-doped with M ions and titanium ions are obtained.
[0016] Preferably, the material containing aluminum ions is at least one of oxides, nitrates, carbonates, acetates and organic polymers containing aluminum ions.
[0017] Preferably, the material containing titanium ions is at least one of oxides, nitrates, carbonates, acetates and organic polymers containing titanium ions.
[0018] Preferably, the material containing M ions is at least one of oxides, nitrates, carbonates, acetates or organic polymers containing M ions.
[0019] Preferably, the temperature of the high temperature solid phase reaction in step (2) is 600°C to 900°C.
[0020] Preferably, the temperature of the secondary high-temperature solid-phase sintering in step (3) is 1000°C to 1100°C.
[0021] A laser gain medium material is prepared by the laser gain medium material preparation method.
[0022] Preferably, the doping concentration of titanium ions in the Al2O3 crystal is 0.2-1 wt.%.
[0023] The principle of the present invention is:
[0024] The present invention co-dopes M ions in a titanium-doped sapphire lattice, and the M ions can effectively adjust the lattice site structure of titanium ions in the crystal, so that the lattice site structure of the titanium ions is relaxed. The lattice site structure relaxation can effectively alleviate the lattice distortion caused by the large difference in radius between titanium ions and aluminum ions, increase the stability of titanium ions in the lattice, and thus greatly increase the doping concentration of titanium ions in the crystal.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0026] (1) The laser gain medium material of the present invention can effectively increase the titanium ion doping concentration in the crystal by introducing M ions, thereby achieving high-concentration titanium ion doping of the crystal, and the titanium ion doping concentration can be adjusted according to actual needs. High-concentration titanium sapphire doped gain medium is very conducive to direct diode pumping to generate broadband tunable lasers, thereby greatly reducing the structural complexity, size and price of existing titanium sapphire doped tunable lasers.
[0027] (2) The laser gain medium material of the present invention, in a method of increasing the doping concentration of titanium ions in alumina of the present invention, co-doping with M ions can effectively alleviate the lattice distortion caused by the large difference in radius between titanium ions and aluminum ions, reduce the stress in the crystal, and on the one hand increase the doping concentration of titanium ions and improve the segregation coefficient of the doped ions; on the other hand, a large segregation coefficient is beneficial to the uniformity of the distribution of doped titanium ions in the crystal, thereby reducing the difficulty of preparing the titanium-doped sapphire gain medium, and is beneficial to the large-size and high-quality preparation of the crystal, providing a gain medium material guarantee for the development of 100-petabawatt or even higher-power lasers. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is the diffuse reflectance spectrum of the sapphire crystal powder co-doped with titanium ions and Be ions according to Example 1 of the present invention.
[0029] Figure 2 This is a comparison diagram of the simulated lattice structures of pure aluminum oxide, titanium ion-single-doped sapphire crystal and titanium ion and Be ion-co-doped sapphire crystal of Example 1 of the present invention.
[0030] Figure 3 This is the diffuse reflectance spectrum of the sapphire crystal powder co-doped with titanium ions and Na ions according to Example 2 of the present invention.
[0031] Figure 4 This is the diffuse reflectance spectrum of the sapphire crystal powder co-doped with titanium ions and K ions according to Example 3 of the present invention.
[0032] Figure 5 This is the titanium ion test concentration at the seed crystal portion of the sapphire crystal co-doped with titanium ions and K ions according to Example 3 of the present invention.
[0033] Figure 6 This is a comparison diagram of the simulated lattice structures of pure aluminum oxide, titanium ion-single-doped sapphire crystals and titanium ion and Mg ion-co-doped sapphire crystals of Example 4 of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0035] Example 1
[0036] Co-doping with divalent Be ions increases the doping concentration of titanium ions in titanium-doped sapphire crystals:
[0037] Press (Al 1-x-y Ti x Be y )2O 3-δ Weigh aluminum oxide, titanium dioxide, and beryllium oxide, where x = 0.01, y = 0.01, and δ = 0.01;
[0038] After the materials are fully ground and mixed, the mixture is synthesized by solid phase reaction at high temperature (900° C.) to obtain sapphire powder co-doped with titanium ions and Be ions.
[0039] The obtained sapphire powder co-doped with titanium ions and Be ions is pressed into a tablet and solid-phase sintered again at high temperature (1050° C.). After sintering, a high-temperature melt crystal is grown by a Czochralski method. After crystal growth is completed, the sapphire crystal co-doped with titanium ions and Be ions is obtained.
[0040] The diffuse reflectance spectrum of the sapphire crystal powder co-doped with titanium ions and Be ions prepared in this embodiment is as follows: Figure 1As shown, the results show that compared with the titanium ion single doped sapphire sample, after co-doping with divalent Be ions, the diffuse reflection intensity of 300-400nm of the co-doped sapphire sample is greatly improved, indicating that the content of the second phase of titanium dioxide in the powder is greatly reduced, which leads to a significant increase in the diffuse reflection intensity of 300-400nm. The doping concentration of titanium ions in the lattice was evaluated by the Kubelka-munk formula, and the results showed that the value was about 0.93%.
[0041] ABINIT software was used to simulate pure alumina crystal, titanium-doped alumina crystal, and sapphire crystal co-doped with titanium ions and Be ions prepared in this embodiment. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that in pure alumina crystals, the aluminum-oxygen bond lengths are 1.87 and 1.99 angstroms, respectively. After titanium ion doping, the bond lengths become 2.10 and 2.00 angstroms, respectively, and the lattice distortion is large. After co-doping with Be ions, the aluminum-oxygen bond length of 2.10 angstroms is shortened to 1.93 angstroms, which is close to 1.87 angstroms of pure alumina. This shows that co-doping with Be ions can effectively alleviate the lattice distortion caused by the large difference in the radius of titanium ions and aluminum ions, which is beneficial to reducing the internal stress of the crystal and increasing the titanium ion doping concentration in titanium-doped sapphire.
[0042] Example 2
[0043] Co-doping with monovalent Na ions increases the doping concentration of titanium ions in titanium-doped sapphire crystals:
[0044] Press (Al 1-x-y Ti x Na y )2O 3-δ Weigh alumina, titanium dioxide, and sodium nitrate, where x = 0.005, y = 0.005, and δ = 0.01;
[0045] After the materials are fully ground and mixed, the mixture is subjected to solid phase reaction synthesis at high temperature (600°C) to obtain sapphire powder co-doped with titanium ions and Na ions;
[0046] The obtained sapphire powder co-doped with titanium ions and Na ions is pressed into a tablet and solid-phase sintered again at high temperature (1000° C.) After sintering, a temperature gradient method is used to grow crystals, and after growth, co-doped crystals are obtained.
[0047] The diffuse reflectance spectrum of the sapphire crystal powder co-doped with titanium ions and Na ions prepared in this example is as follows: Figure 3As shown, the results show that compared with the titanium ion single doped sapphire sample, after co-doping with monovalent Na ions, the diffuse reflection intensity of 300-400nm of the co-doped sapphire sample is greatly improved, indicating that the content of the second phase of titanium dioxide in the powder is greatly reduced, that is, the monovalent Na ions promote more titanium ions to enter the sapphire lattice, which leads to a significant increase in the diffuse reflection intensity of 300-400nm. The doping concentration of titanium ions in the lattice was evaluated by the Kubelka-munk formula, and the results showed that the value was about 0.4%.
[0048] Example 3
[0049] Co-doping with monovalent K ions increases the doping concentration of titanium ions in titanium-doped sapphire crystals:
[0050] Press (Al 1-x-y Ti x K y )2O 3-δ Alumina, titanium dioxide and potassium carbonate were weighed to prepare three groups of samples, namely, crystal 1: x = 0.003, y = 0.00, δ = 0.00; crystal 2: x = 0.003, y = 0.001, δ = 0.002; crystal 3: x = 0.003, y = 0.003, δ = 0.006.
[0051] After the materials are fully ground and mixed, the mixture is synthesized by solid phase reaction at high temperature (750°C) to obtain sapphire powder co-doped with titanium ions and K ions.
[0052] The obtained sapphire powder co-doped with titanium ions and K ions is pressed into a tablet and solid-phase sintered again at high temperature (1100° C.). After sintering, a temperature gradient method is used to grow a high-temperature melt crystal. After the crystal growth is completed, the sapphire crystal co-doped with titanium ions and K ions is obtained.
[0053] The diffuse reflectance spectrum of the sapphire crystal powder (crystal 3) co-doped with titanium ions and K ions prepared in this example is as follows: Figure 4 As shown in the figure, the results show that compared with the titanium ion single doped sapphire sample, after co-doping with monovalent K ions, the diffuse reflection intensity of 300-400nm of the co-doped sapphire sample is greatly improved, indicating that the content of the second phase of titanium dioxide in the powder is greatly reduced, that is, the monovalent K ions promote more titanium ions to enter the sapphire lattice, which leads to a significant increase in the diffuse reflection intensity of 300-400nm. The doping concentration of titanium ions in the lattice was evaluated by the Kubelka-munk formula, and the results showed that the value was about 0.3%.
[0054] The sapphire crystal seed crystal part co-doped with titanium ions and K ions prepared in this embodiment was selected, and the doping concentration was tested using an inductively coupled plasma emission spectrometer. The concentration test results of crystals 1-3 are as follows: Figure 5As shown. It can be seen that with the addition of K ions, the titanium ion test concentration in the crystal is greatly increased. Compared with the sapphire crystal sample doped with titanium alone (titanium ion doping concentration is 0.3%, the actual test is 0.05%), the introduction of a small amount of K ions increases the actual titanium ion test concentration by nearly 3 times. By continuing to increase the K ion doping amount, the titanium ion concentration of the co-doped crystal sample increases by nearly 5 times to 0.28%. This shows that K ions can effectively adjust the doping concentration of titanium ions in the crystal.
[0055] Example 4
[0056] Co-doping with divalent Mg ions increases the doping concentration of titanium ions in titanium-doped sapphire crystals:
[0057] Press (Al 1-x-y Ti x Mg y )2O 3-δ Weigh aluminum oxide, titanium dioxide, and magnesium carbonate, where x = 0.007, y = 0.007, and δ = 0.007;
[0058] After the materials are fully ground and mixed, the mixture is synthesized by solid phase reaction at high temperature (800° C.) to obtain sapphire powder co-doped with titanium ions and Mg ions.
[0059] The obtained sapphire powder co-doped with titanium ions and Mg ions is pressed into a tablet and then solid-phase sintered at high temperature (1100°C). After sintering, a high-temperature melt crystal is grown by a Czochralski method. After the crystal growth is completed, a sapphire crystal co-doped with titanium ions and Mg ions is obtained.
[0060] ABINIT software was used to simulate pure alumina crystal, titanium-doped alumina crystal, and sapphire crystal co-doped with titanium ions and Mg ions prepared in this embodiment. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that in pure alumina crystals, the aluminum-oxygen bond lengths are 1.87 and 1.99 angstroms, respectively. After titanium ion doping, the bond lengths become 2.10 and 2.00 angstroms, respectively, and the lattice distortion is large. After co-doping with Mg ions, the aluminum-oxygen bond length of 2.10 angstroms is shortened to 1.96 angstroms, which is close to 1.87 angstroms of pure alumina. This shows that co-doping with Mg ions can effectively alleviate the lattice distortion caused by the large difference in the radius between titanium ions and aluminum ions, which is beneficial to reducing the internal stress of the crystal and increasing the titanium ion doping concentration in titanium-doped sapphire.
[0061] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a laser gain medium material, characterized in that: The following steps are involved: (1) Press (Al 1-x-y Ti x M y )2O 3-δ Weighing materials containing aluminum ions, materials containing titanium ions, and materials containing M ions; The M ions are used to adjust the doping concentration of titanium ions in the Al2O3 crystal, which is Be 2+ 、Na + , K + Mg 2+ , Rb + , Ca 2+ , Sr 2+ , Ba 2+ One or any combination of x = 0.10%~1%, which is the molar percentage of titanium ions in the total cations; y = 0.10%~1%, which is the molar percentage of M ions in the total cations; δ is the change in the number of oxygen ions caused by the change in the valence state of M ions, δ>0%; (2) grinding and mixing the materials weighed in step (1) and subjecting them to a high-temperature solid-phase reaction to obtain sapphire powder co-doped with M ions and titanium ions; (3) Pressing the sapphire powder co-doped with M ions and titanium ions into tablets and performing secondary high-temperature solid-phase sintering; (4) A high temperature melt crystal growth method is used to grow crystals to obtain sapphire crystals co-doped with M ions and titanium ions.
2. The method for preparing a laser gain medium material according to claim 1, characterized in that: The material containing aluminum ions is at least one of oxides, nitrates, carbonates, acetates and organic polymers containing aluminum ions.
3. The method for preparing a laser gain medium material according to claim 1, characterized in that: The material containing titanium ions is at least one of oxides, nitrates, carbonates, acetates and organic polymers containing titanium ions.
4. The method for preparing a laser gain medium material according to claim 1, characterized in that: The material containing M ions is at least one of oxides, nitrates, carbonates, acetates or organic polymers containing M ions.
5. The method for preparing a laser gain medium material according to claim 1, characterized in that: The temperature of the high temperature solid phase reaction in step (2) is 600°C to 900°C.
6. The method for preparing a laser gain medium material according to claim 1, characterized in that: The temperature of the secondary high-temperature solid-phase sintering in step (3) is 1000°C~1100°C.
7. A laser gain medium material, characterized in that: The laser gain medium material is prepared by the preparation method of the laser gain medium material according to any one of claims 1 to 6.
8. The laser gain medium material according to claim 7, characterized in that: The doping concentration of titanium ions in Al2O3 crystals is 0.2~1wt.%.
Citation Information
Patent Citations
Large-size titanium-doped sapphire laser crystal and manufacturing process thereof
CN108048908A
Co-doped gallium oxide crystal laser material with high thermal conductivity and high electric conductivity and preparation method thereof
CN109183150A